Current State and Prospects of Development of the Sports System of Ukraine: Legal Aspects (Estado actual y perspectivas de desarrollo del sistema deportivo de Ucrania: aspectos legales) - Maxym Tkalych; Iryna Davydova; Yuliia Tolmachevska (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The article analyzes the current state of the sports organization system in Ukraine. The authors of the article argue that the sports system in Ukraine needs to be reformed in light of current trends in world sports. First and foremost, the need for regulatory and institutional development of the professional sport, which can have a positive impact on the development of the entire sports system of Ukraine. Currently, the dominant position in Ukrainian sport is occupied by the state and non-governmental organizations. This approach was justified under the conditions of a planned economy during the Soviet Union, but it is now outdated and hinders the development of Ukrainian sport.